(untitled) - Nitobe, Inazo (Rutland, 1969)
Very strongly recommended reading for students of Japanese cultural history and the martial arts, Bushido: The Soul of Japan is a powerful presentation and a moving book with ideas as relevant today as they were 100 years ago
Keywords: Bushido